2002
DOI: 10.1345/aph.1a158
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pharmacist-Managed Lipid Clinic

Abstract: A pharmacist-managed lipid clinic can be developed and integrated into a primary care medical clinic. Pharmacists can effectively manage lipid-lowering therapy, helping to achieve LDL goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
4
33
0
Order By: Relevance
“…However, the study's findings are consistent with those of prior research documenting favorable effects of physician-pharmacist collaboration on patients with chronic disease. [17][18][19][20][21][22] ■■ Conclusions Compared with usual care provided by physicians only, physician-pharmacist collaboration improved 6-month outcomes in a sample of patients with metabolic syndrome attending family medicine clinics in a teaching hospital in the Middle East. The effects of careful periodic pharmacological and dietary screening, education, and monitoring of metabolic syndrome should be assessed in routine health care provided in a variety of health care system settings.…”
Section: Disclosuresmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the study's findings are consistent with those of prior research documenting favorable effects of physician-pharmacist collaboration on patients with chronic disease. [17][18][19][20][21][22] ■■ Conclusions Compared with usual care provided by physicians only, physician-pharmacist collaboration improved 6-month outcomes in a sample of patients with metabolic syndrome attending family medicine clinics in a teaching hospital in the Middle East. The effects of careful periodic pharmacological and dietary screening, education, and monitoring of metabolic syndrome should be assessed in routine health care provided in a variety of health care system settings.…”
Section: Disclosuresmentioning
confidence: 95%
“…[13][14][15][16] The role of clinical pharmacists in improving treatment outcomes; achieving therapeutic goals; lowering adverse reactions or undesirable effects; and reducing medication costs in many chronic medical conditions, such as hypertension, diabetes mellitus, heart failure, and dyslipidemia, has been demonstrated by many studies using different designs. [17][18][19][20][21][22] However, studies of the pharmacist's role in the management of metabolic syndrome have been limited to screening for metabolic syndrome in community pharmacy patrons without CHD and in patients receiving antipsychotics. 23,24 In the present study, a pharmaceutical care program was developed, allowing 1 clinical pharmacist to work at a physician's practice site to assess and manage the components of metabolic syndrome.…”
Section: A Randomized Controlled Trial To Assess Pharmacist-physicianmentioning
confidence: 99%
See 1 more Smart Citation
“…S tudies have shown that pharmacist consultation programs can improve clinical outcomes by optimizing medication use in ambulatory patients. [1][2][3][4][5] Among patients in a heart failure clinic, a program of pharmacist evaluation (medication evaluation and recommendations, patient education and followup telemonitoring) resulted in a significant decrease in heart failure events and all-cause mortality. Study authors attributed this result to closer follow-up and optimizing doses of angiotensinconverting enzyme (ACE) inhibitors.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…2 Collaboration between physicians and pharmacists has resulted in a higher rate of patients meeting their lipid-level goals than previously achieved without collaboration in the same practice. 4 The Asheville Project demonstrated that close collaboration between community pharmacists and patients with diabetes mellitus was associated with improved blood sugar management. 5 The National Committee for Quality Assurance's key program for quality measurement is the Healthcare Effectiveness Data and Information Set (HEDIS).…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%